Hesperidin: A Potential Therapeutic Agent against COVID-19 - Dhingra, Ashwani K.; Chopra, Bhawna; Rathi, Vaibhav; Sapra, Sameer (Current Drug Discovery Technologies, 2023)
COVID-19, aka Coronavirus Disease 2019, triggered by new severe acute respiratory syndrome coronavirus-2 or SARS-CoV-2, is now a public health emergency due to its rapid spread, high transmission efficiency, and severe viral pandemic that is significantly increasing the number of patients and associated deaths. Currently, no specific treatment is available for this highly contagious virus. The unavailability of effective and specific treatments and the severity of this epidemic situation potentiate medicinal chemists’ in supporting new prophylactic or therapeutic interventions against COVID-19. This study discusses the therapeutic potential of hesperidin, a traditionally used herbal medicine with an exceptional safety profile. Recent studies on hesperidin advocate its promising potential in the prevention and management of COVID-19. This paper also discusses the recent clinical studies based on the previously documented antiviral activity of hesperidin. Herein, we propose the detailed preclinical and clinical manifestations of hesperidin based on its multifaceted bioactivities to develop a novel anti-COVID-19 lead.
Keywords: immunomodulatory